Effect of Teacher Professional Development on Student Academic Performance in Mathematics in United States - Ride, Sally (Journal of Education and Practice, 2026)
Purpose: The purpose of this article was to analyze effect of teacher professional development on student academic performance in mathematics. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research indicates that teacher professional development (TPD) positively impacts student performance in mathematics when the training is sustained and content-focused. Studies show that teachers who participate in ongoing, collaborative PD programs tend to improve their teaching practices, leading to higher student achievement in math. Effective TPD, particularly coaching and regular training, has been found to significantly enhance student math scores, especially in long‑term studies Unique Contribution to Theory, Practice and Policy: Social cognitive theory (SCT), constructivist learning theory & theory of planned behavior may be used to anchor future studies on the effect of teacher professional development on student academic performance in mathematics. In practice, it is critical that professional development (PD) programs for mathematics teachers emphasize sustained engagement rather than short-term workshops. From a policy perspective, it is important for education policymakers to ensure that teacher professional development is not only mandatory but also well-supported in terms of resources, funding, and infrastructure.